2018
DOI: 10.1051/ocl/2018043
|View full text |Cite
|
Sign up to set email alerts
|

The concept of sphingolipid rheostat in skin: a driving force for new active ingredients in cosmetic applications

Abstract: Skin is a representative model of the complex metabolism that lipids may trigger. It is known that the biosynthesis of these lipids in mammalian cells generally ensures the cell membranes stability and participates to the signaling function. In the inner layers of the skin, the “de-novo” synthesis is the driving force ensuring proliferation, development and intercellular signaling. To promote stratum corneum formation, lipid catabolism leads to the renewal of ceramides, fatty acids and cholesterol that are res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Coupled decrease in the levels of cerebrosides were also related to a decrease in the structural integrity of cell membranes and shrinkage of body walls [53]. Outside their physiological significance, the benefits of sphingolipids on skin have been extensively studied [61]. Duan, et al (2016), reported the digestion and absorption of dietary cerebrosides into ceramides that facilitate wound healing and improved skin barrier function in mice [62].…”
Section: Plos Onementioning
confidence: 99%
“…Coupled decrease in the levels of cerebrosides were also related to a decrease in the structural integrity of cell membranes and shrinkage of body walls [53]. Outside their physiological significance, the benefits of sphingolipids on skin have been extensively studied [61]. Duan, et al (2016), reported the digestion and absorption of dietary cerebrosides into ceramides that facilitate wound healing and improved skin barrier function in mice [62].…”
Section: Plos Onementioning
confidence: 99%
“…compared to fish injected with PBS and sampled at the same time. SMs are sphingolipids that are mainly concentrated in the caveolae of the cell membrane of adipocytes and in the lipid rafts of macrophages, in both cases performing specialized functions that can modulate the inflammatory response [73,74]. These functions could include cell signalling, and participation in clathrin-independent processes of endocytosis, phagocytosis and apoptosis [73,74].…”
Section: Famesmentioning
confidence: 99%
“…SMs are sphingolipids that are mainly concentrated in the caveolae of the cell membrane of adipocytes and in the lipid rafts of macrophages, in both cases performing specialized functions that can modulate the inflammatory response [73,74]. These functions could include cell signalling, and participation in clathrin-independent processes of endocytosis, phagocytosis and apoptosis [73,74]. Thus, the function of SM could be linked to the activation of regulatory mechanisms such as apoptosis of immune cells that have already fulfilled their function at the site of inflammation to avoid excessive inflammation, and their subsequent elimination by phagocytosis.…”
Section: Famesmentioning
confidence: 99%
“…Over the last decade, a variety of studies have proven the efficiency of a PUFA-rich diet in optimizing the skin barrier function [ 18 , 19 , 20 ]. In fact, the physical structure of the barrier function is dependent on LA, since it was reported that the SC contains large amounts of sphingolipids rich in linoleate content [ 21 ]. Additionally, bioactive lipids derived from both n-3 and n-6 PUFAs regulate several biological pathways in the skin and might be involved in the formation of the SC, even though the exact underlying mechanisms are still not understood [ 18 , 22 ].…”
Section: Introductionmentioning
confidence: 99%